A kind of acid and alkali resistant fluororubber and its preparation method and application
By crosslinking the double ligand Zn-MOF in the modified composite filler with epoxycyclohexyl-cage polysilsesquioxane and adding acidified carbon nanotubes to form a stable three-dimensional crosslinking structure, the problem of poor durability of fluoroelastomer in an acid-base environment is solved, and its acid-base resistance and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202411078056.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The poor durability of fluoroelastomer in an acid-base environment leads to a deterioration of sealing performance. The existing crosslinking agents are unstable under acid-base conditions, affecting the acid-base resistance of fluoroelastomer.
Modified composite filler is used to synthesize the biligand Zn-MOF by hydrothermal, and crosslink it with epoxycyclohexyl-cage polysilsesquioxane, and acidified carbon nanotubes and ethylenediamine are added to form a stable three-dimensional crosslinking structure to improve the acid and alkali resistance of fluoroelastomer.
It significantly improves the acid and alkali resistance and mechanical properties of fluoroelastic rubber, reduces the aging effect of acid gas on fluoroelastic rubber, and is suitable for electric vehicle battery sealing rubber.
Smart Images

Figure BDA0004982921610000081 
Figure BDA0004982921610000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluororubber, and in particular relates to an acid- and alkali-resistant fluororubber and a preparation method and application thereof. Background Art
[0002] Fluororubber has excellent heat resistance, oxidation resistance, oil resistance, and atmospheric aging resistance. Although fluororubber has high chemical stability, it is not resistant to amine, ammonia, hydrofluoric acid, chlorosulfonic acid, and phosphoric acid hydraulic oils, and its acid and alkali resistance is slightly weak. After long-term use in acid and alkali, the performance of fluororubber will decrease, thus affecting the sealing performance of fluororubber. Inorganic fillers can improve the performance of fluororubber. Carbon black N990 is currently the most commonly used reinforcing filler for fluororubber, and has good comprehensive performance, but carbon black N990 cannot improve the acid and alkali resistance of fluororubber.
[0003] Peroxide initiators are widely used in the vulcanization and cross-linking process of fluororubber. The peroxide vulcanization process can significantly improve the corrosion resistance of fluororubber in corrosive media. Currently, the bisphenol vulcanization system is mainly used, but it requires the participation of calcium hydroxide. Calcium hydroxide will swell in acidic media and affect the sealing performance of fluororubber.
[0004] Patent CN103509215A discloses a marine chloroprene / tetrafluoroethylene rubber composite cable sheath material and a preparation method thereof, wherein tetrafluoroethylene rubber and chloroprene rubber are mixed with carbon black N990, and cross-linked under the action of a cross-linking aid to obtain a fluororubber with good properties such as acid and alkali resistance, oil resistance, heat aging resistance, and weather resistance. However, the cross-linking aid of this solution is an ester compound, and the formed ester bond is unstable and easily decomposed under acid and alkali conditions, so that the cross-linking network is destroyed, resulting in reduced sealing of the fluororubber. Summary of the invention
[0005] The object of the present invention is to provide an acid- and alkali-resistant fluororubber and a preparation method thereof, so as to solve the problem that the fluororubber has poor acid- and alkali-resistant ability after peroxide vulcanization.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An acid and alkali resistant fluororubber, comprising the following raw materials in parts by mass:
[0008] 100-120 parts of fluorinated rubber, 10-20 parts of tetrapropylene fluororubber, 4-6 parts of benzoyl peroxide, 20-25 parts of modified composite filler;
[0009] The modified composite filler is prepared by the following steps:
[0010] The dual ligand Zn-MOF, epoxy cyclohexyl-cage polysilsesquioxane and dimethyl sulfoxide are mixed in a reaction kettle, and magnetic stirring is carried out at 75-85° C. for 6-8 hours under nitrogen protection. Then sodium p-hydroxybenzenesulfonate is added to the reaction kettle, and the temperature is raised to 110-120° C. for reaction for 3-4 hours. Then, acidified carbon nanotubes are added to the reaction kettle, and the reaction is carried out at a constant temperature for 1-2 hours. After cooling to room temperature, ethylenediamine is added, and the reaction is stirred for 18-24 hours. After centrifugation, the mixture is washed with deionized water and ethanol respectively, and vacuum dried at 70-80° C. to constant weight to obtain a modified composite filler.
[0011] Furthermore, the usage ratio of the dual ligand Zn-MOF, epoxy cyclohexyl-cage polysilsesquioxane, dimethyl sulfoxide, sodium p-hydroxybenzenesulfonate, acidified carbon nanotubes and ethylenediamine is 5-8 g: 2-3 g: 80-100 mL: 0.5-1 g: 5-8 g: 150-200 mL.
[0012] Furthermore, the dual-ligand Zn-MOF is prepared by the following steps:
[0013] In a reaction kettle, 2-hydroxybenzimidazole and polyvinyl pyrrolidone are dissolved in methanol respectively and mixed, and then zinc nitrate hexahydrate is dissolved in methanol and dripped into the reaction kettle and stirred. The mixture is stirred at 65-75° C. for 1-2 hours, and the solid is collected after centrifugation. The solid is washed with methanol and vacuum dried to obtain a dual-ligand Zn-MOF.
[0014] Furthermore, the usage ratio of 2-hydroxybenzimidazole, polyvinyl pyrrolidone and zinc nitrate hexahydrate is 3-6g:8-10g:12-15g.
[0015] Further, the acidified carbon nanotubes are prepared by the following steps:
[0016] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1 to prepare a mixed acid solution, and then multi-walled carbon nanotubes are mixed with the mixed acid solution in a dosage ratio of 1 g: 100 mL, and ultrasonic stirring is performed at a temperature of 50-60° C. for 2-3 hours, and a precipitate is obtained by centrifugation, and the acidified carbon nanotubes are obtained after washing and vacuum drying.
[0017] A method for preparing acid- and alkali-resistant fluororubber comprises the following steps:
[0018] Step 1, mixing fluorinated rubber and tetrafluoroethylene rubber on an open mill at 60-65° C. for 4-6 minutes to obtain a mixed rubber, adding the modified composite filler to the mixed rubber at 80-95° C. for 6-8 minutes, and then adding benzoyl peroxide at 100-110° C. for 3-5 minutes to obtain a mixed rubber;
[0019] Step 2: Roll the mixed rubber on an open rubber mixer with a thickness of 2-4 mm. Place the mixed rubber on a open mixer for 12-16 hours and then thin it in a triangle bag on the mixer for 10-15 times. Vulcanize the sample on a 45T flat vulcanizer, vulcanize at 173-177°C for 10 minutes and at 230°C for 24 hours to obtain acid and alkali resistant fluororubber.
[0020] Application of acid and alkali resistant fluororubber in electric vehicle battery sealing rubber.
[0021] Beneficial effects of the present invention:
[0022] (1) The acid- and alkali-resistant fluororubber prepared by the present invention is vulcanized with peroxide to uniformly disperse the alkaline modified composite filler in the fluororubber, thereby improving the physical and mechanical properties of the fluororubber. The alkaline modified composite filler not only reduces the aging effect of the acid gas generated during the vulcanization process on the fluororubber, but also improves the acid resistance of the fluororubber after vulcanization, and can be well applied in the field of sealing rubber for electric vehicle batteries.
[0023] (2) The present invention reacts the co-crosslinking agent epoxy cyclohexyl-cage polysilsesquioxane with the dual ligand Zn-MOF to crosslink, and adds sodium hydroxybenzenesulfonate to form a more stable three-dimensional crosslinking structure, so that the dual ligand Zn-MOF is firmly combined with the co-crosslinking agent, and the carboxyl groups on the surface of the acidified carbon nanotubes are reacted with the hydroxyl groups to covalently combine the easily agglomerated carbon nanotubes in the three-dimensional crosslinking structure, so that the obtained modified composite filler has excellent dispersibility in fluororubber, thereby improving the mechanical properties of the fluororubber.
[0024] (3) The modified composite filler prepared by the present invention has a hydroxyl group and an alkaline N-heterocycle, which enables the modified composite filler to react with acid, thereby reducing the destructive effect of the acid on the fluororubber structure. The acidic carbon nanotubes in the modified composite filler also have the ability to react with acid after being modified with amino groups. The synergistic effect of the two improves the acid and alkali resistance of the fluororubber, and the good dispersibility of the modified composite filler also improves the physical properties of the fluororubber. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: A method for preparing an acid- and alkali-resistant fluororubber, comprising the following steps:
[0027] Step 1. In a reaction kettle, dissolve 3 g of 2-hydroxybenzimidazole and 8 g of polyvinyl pyrrolidone in 80 mL of methanol respectively and mix them. Then dissolve 12 g of zinc nitrate hexahydrate in 100 mL of methanol and drip into the reaction kettle and stir. Stir at 65 ° C for 1 h, centrifuge at 8000 rpm for 20 min, collect the solid, wash it twice with methanol, and vacuum dry it at 60 ° C for 12 h to obtain a dual-ligand Zn-MOF.
[0028] Step 2: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 to prepare a mixed acid solution, take 8 g of multi-walled carbon nanotubes and mix them with 800 mL of the mixed acid solution, react with ultrasonic stirring at 50°C for 2 hours, centrifuge to obtain a precipitate, wash with deionized water until the pH value of the last washing solution is neutral, then wash with anhydrous ethanol, and vacuum dry at 50°C to constant weight to obtain acidified carbon nanotubes.
[0029] Step 3: Mix 5 g of dual-ligand Zn-MOF, 2 g of epoxycyclohexyl-cage polysilsesquioxane and 80 mL of dimethyl sulfoxide in a reactor, stir magnetically at 75 ° C for 6 h under nitrogen protection, add 0.5 g of sodium p-hydroxybenzenesulfonate to the reactor, heat to 110 ° C and react for 3 h, then add 5 g of acidified carbon nanotubes to the reactor, react at a constant temperature for 1 h, cool to room temperature, add 150 mL of ethylenediamine, stir and react for 18 h, centrifuge, wash with deionized water and ethanol respectively, and vacuum dry at 70 ° C to constant weight to obtain a modified composite filler.
[0030] Step 4: Mix 100g of fluororubber and 10g of tetrapropylene fluororubber on an open mixing mill at 60°C for 4min to obtain a mixed rubber; take 20g of the modified composite filler and add it to the mixed rubber, mix it at 80°C for 6min; then add 4g of benzoyl peroxide and mix it at 100°C for 3min to obtain a mixed rubber; roll the mixed rubber on an open mixing mill with a thickness of 2mm and ventilate it for 12h; finally, re-mix and thin it in a triangular bag on the open mixing mill for 10 times; vulcanize the sample with a 45T flat vulcanizer, vulcanize it at 173°C for 10min in the first stage and at 230°C for 24h in the second stage to obtain acid and alkali resistant fluororubber.
[0031] Embodiment 2: A method for preparing an acid- and alkali-resistant fluororubber, comprising the following steps:
[0032] Step 1. In a reaction kettle, dissolve 4.5 g of 2-hydroxybenzimidazole and 9 g of polyvinyl pyrrolidone in 90 mL of methanol respectively and mix them. Then dissolve 13.5 g of zinc nitrate hexahydrate in 110 mL of methanol and drip into the reaction kettle and stir. Stir at 70 ° C for 1.5 h, centrifuge at 9000 rpm for 25 min, collect the solid, wash it twice with methanol, and vacuum dry it at 65 ° C for 14 h to obtain a dual-ligand Zn-MOF.
[0033] Step 2: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 to prepare a mixed acid solution, take 9 g of multi-walled carbon nanotubes and mix them with 900 mL of the mixed acid solution, react with ultrasonic stirring at 55°C for 2.5 hours, centrifuge to obtain a precipitate, wash with deionized water until the pH value of the last washing solution is neutral, then wash with anhydrous ethanol, and vacuum dry at 55°C to constant weight to obtain acidified carbon nanotubes.
[0034] Step 3: Mix 6.5 g of dual-ligand Zn-MOF, 2.5 g of epoxycyclohexyl-cage polysilsesquioxane and 90 mL of dimethyl sulfoxide in a reactor, stir magnetically at 80 ° C for 7 h under nitrogen protection, add 0.75 g of sodium p-hydroxybenzenesulfonate to the reactor, heat to 115 ° C and react for 3.5 h, then add 6.5 g of acidified carbon nanotubes to the reactor, react at a constant temperature for 1.5 h, cool to room temperature, add 175 mL of ethylenediamine, stir and react for 21 h, centrifuge, wash with deionized water and ethanol respectively, and vacuum dry at 75 ° C to constant weight to obtain a modified composite filler.
[0035] Step 4, 110g of fluororubber and 15g of tetrapropylene fluororubber are mixed at 62.5°C for 5min on an open mixing mill to obtain a mixed rubber, 22.5g of modified composite filler is added to the mixed rubber and mixed at 90°C for 7min, then 5g of benzoyl peroxide is added and mixed at 105°C for 4min to obtain a mixed rubber, the mixed rubber is sheeted on an open mixing mill with a thickness of 3mm, and ventilated for 14h, and finally re-mixed in the form of a triangular bag on the mixing mill for 12 times, and the sample is vulcanized on a 45T flat vulcanizer, with a first-stage vulcanization at 175°C for 10min and a second-stage vulcanization at 230°C for 24h to obtain acid and alkali resistant fluororubber.
[0036] Embodiment 3: A method for preparing an acid- and alkali-resistant fluororubber, comprising the following steps:
[0037] Step 1. In a reaction kettle, dissolve 6 g of 2-hydroxybenzimidazole and 10 g of polyvinyl pyrrolidone in 100 mL of methanol respectively and mix them. Then dissolve 15 g of zinc nitrate hexahydrate in 120 mL of methanol and drip into the reaction kettle and stir. Stir at 75 ° C for 2 h, centrifuge at 10000 rpm for 30 min, collect the solid, wash it with methanol 3 times, and vacuum dry it at 70 ° C for 6 h to obtain a dual-ligand Zn-MOF.
[0038] Step 2: Mix concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 to prepare a mixed acid solution, take 0g of multi-walled carbon nanotubes and mix them with 1000mL of the mixed acid solution, react with ultrasonic stirring at 60°C for 3h, centrifuge to obtain a precipitate, wash with deionized water until the pH value of the last washing liquid is neutral, then wash with anhydrous ethanol, and vacuum dry at 60°C to constant weight to obtain acidified carbon nanotubes.
[0039] Step 3: Mix 8 g of dual-ligand Zn-MOF, 3 g of epoxycyclohexyl-cage polysilsesquioxane and 100 mL of dimethyl sulfoxide in a reactor, and stir magnetically at 85 ° C for 8 h under nitrogen protection. Then add 1 g of sodium p-hydroxybenzenesulfonate to the reactor, heat to 120 ° C and react for 4 h, and then add 8 g of acidified carbon nanotubes to the reactor, react at a constant temperature for 2 h, cool to room temperature, add 200 mL of ethylenediamine, stir and react for 24 h, centrifuge, wash with deionized water and ethanol respectively, and vacuum dry at 80 ° C to constant weight to obtain a modified composite filler.
[0040] Step 4: Mix 120g of fluororubber and 20g of tetrapropylene fluororubber on an open mixing mill at 65°C for 6min to obtain a mixed rubber; take 25g of the modified composite filler and add it to the mixed rubber, mix it at 95°C for 8min; then add 6g of benzoyl peroxide and mix it at 110°C for 5min to obtain a mixed rubber; roll the mixed rubber on an open mixing mill with a thickness of 4mm; ventilate and place it for 16h; finally, re-mix and thin it in a triangular bag on the open mixing mill for 15 times; vulcanize the sample with a 45T flat vulcanizer, vulcanize it at 177°C for 10min in the first stage and at 230°C for 24h in the second stage to obtain acid and alkali resistant fluororubber.
[0041] Principle of the invention:
[0042] The invention uses 2-hydroxybenzimidazole and polyvinyl pyrrolidone containing hydroxyl groups as ligands to hydrothermally synthesize a dual-ligand Zn-MOF. Polyvinyl pyrrolidone and 2-hydroxybenzimidazole have strong hydrogen bonding and good compatibility, and can be used as dual-ligands of Zn-MOF. The hydroxybenzimidazole ligand in the dual-ligand Zn-MOF is cross-linked with epoxycyclohexyl-cage polysilsesquioxane in dimethyl sulfoxide. The high reactivity of epoxy groups to hydroxyl groups is utilized to form a stable Zn-MOF of 2-hydroxybenzimidazole, epoxycyclohexyl-cage polysilsesquioxane and sodium hydroxybenzenesulfonate in the polymer. A three-dimensional cross-linked structure is defined, so that the epoxy cyclohexyl-cage polysilsesquioxane and the dual ligand Zn-MOF are more tightly and firmly cross-linked, and then the acidified carbon nanotubes rich in carboxyl groups on the surface react with the remaining hydroxyl groups to covalently bind the acidified carbon nanotubes in the three-dimensional cross-linked structure. The addition of ethylenediamine can graft amino groups on the remaining carboxyl groups on the surface of the acidified carbon nanotubes to make the modified composite filler alkaline. The dual ligand Zn-MOF also contains basic N-heterocycles, which have the ability to react with acid, and can consume the acid reaction, weaken the reaction of acid to fluororubber, thereby improving the acid resistance of fluororubber.
[0043] Since fluorine atoms and hydroxide ions repel each other, fluorine rubber itself has good alkali resistance. Fluorine rubber vulcanized by peroxide has better acid and alkali resistance and is more suitable for sealing rubber in electric vehicle battery electrolyte.
[0044] Epoxycyclohexyl-cage polysilsesquioxane can be used as a cross-linking agent to react with fluororubber and tetrafluoropropylene rubber. The mixed rubber of fluororubber and tetrafluoropropylene rubber can improve the mechanical properties and aging resistance of fluororubber. Utilizing the excellent dispersibility and cross-linking properties of epoxycyclohexyl-cage polysilsesquioxane in fluororubber and tetrafluoropropylene rubber, the double ligand Zn-MOF and covalently bonded carbon nanotubes that form a stable three-dimensional cross-link with epoxycyclohexyl-cage polysilsesquioxane are uniformly dispersed in the fluororubber and tetrafluoropropylene rubber blend system to improve the physical properties and acid and alkali resistance of fluororubber. The peroxide benzoyl peroxide will produce fluorinated benzoic acid that accelerates rubber aging during the vulcanization process. The generated fluorinated benzoic acid will react when it contacts the modified composite filler, thereby reducing the aging effect of the fluorinated benzoic acid on fluororubber and improving the aging resistance of fluororubber.
[0045] Comparative Example 1: The difference from Example 1 is that the modified composite filler is prepared by the following steps:
[0046] In a reactor, 5 g of dual-ligand Zn-MOF, 2 g of epoxycyclohexyl-cage polysilsesquioxane and 80 mL of dimethyl sulfoxide were mixed and magnetically stirred at 75 ° C for 6 h under nitrogen protection. Then 0.5 g of sodium p-hydroxybenzenesulfonate was added to the reactor, the temperature was raised to 110 ° C and reacted for 3 h. Then 5 g of multi-walled carbon nanotubes were added to the reactor and reacted at a constant temperature for 1 h. After centrifugation, deionized water and ethanol washing respectively, the mixture was vacuum dried at 70 ° C to constant weight to obtain a modified composite filler.
[0047] Comparative Example 2: The difference from Example 1 is that the dual-ligand Zn-MOF is Zif-8.
[0048] Comparative Example 3: The difference from Example 1 is that sodium p-hydroxybenzene sulfonate is not added in the preparation step of the modified composite filler.
[0049] The sources of some chemical reagents in the embodiments and comparative examples are as follows:
[0050] Zinc nitrate hexahydrate, methanol, ethanol, concentrated sulfuric acid, concentrated nitric acid, and polyvinyl pyrrolidone were purchased from Sigma-Aldrich.
[0051] Sodium p-hydroxybenzenesulfonate was purchased from Wuhan Smack Biotechnology Co., Ltd.
[0052] Benzoyl peroxide was purchased from MacLean Reagent Co., Ltd.
[0053] Tetrafluoroethylene rubber was purchased from Hechuang Polymer Technology (Guangdong) Co., Ltd.
[0054] Fluororubber was purchased from Zhonghao Chenguang Chemical Research Institute Co., Ltd.
[0055] Multi-walled carbon nanotubes with a diameter of 40-60 nm and a length of 20 μm were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0056] Epoxycyclohexyl-cage polysilsesquioxane was purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0057] 2-Hydroxybenzimidazole was purchased from Shandong Poly Chemical Co., Ltd.
[0058] For Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3, the tensile strength and elongation at break were tested by a universal tensile testing machine at room temperature according to GB / T528-2009 standard, and the hardness was tested according to GB / T531-2008. The samples were immersed in 20wt% hydrochloric acid solution and 20wt% sodium hydroxide solution for 48h at an oven temperature of 120°C, and the sample properties were tested. The change rate of tensile strength and the change rate of elongation at break were calculated. The test results are shown in Table 1:
[0059] Table 1
[0060]
[0061]
[0062] As can be seen from Table 1, the performance of Examples 1 to 3 prepared by the present invention is excellent, the change rate of tensile strength and the change rate of elongation at break after acid and alkali immersion are small, and they have excellent acid and alkali resistance and mechanical properties. In Comparative Example 1, due to the direct addition of carbon nanotubes, the carbon nanotubes are not cross-linked with the modified composite filler, resulting in uneven dispersion of the carbon nanotubes in the fluororubber, weakening the mechanical properties of the fluororubber; in Comparative Example 2, due to the change of the ligand of MOF, the cross-linking effect in the modified composite filler is greatly reduced, resulting in the difficulty of dispersing the modified composite filler in the fluororubber, and the mechanical properties of the prepared fluororubber are poor and not resistant to acid and alkali; in Comparative Example 3, due to the lack of sodium p-hydroxybenzenesulfonate in the modified composite filler, the cross-linking strength of the modified composite filler is weak, resulting in partial shedding of the dual-ligand MOF and carbon nanotubes, resulting in weakened mechanical properties and acid and alkali resistance of the fluororubber.
[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An acid and alkali resistant fluororubber, characterized in that: The following raw materials are included by mass: 100-120 parts of fluorinated rubber, 10-20 parts of tetrapropylene fluororubber, 4-6 parts of benzoyl peroxide, 20-25 parts of modified composite filler; The modified composite filler is prepared by the following steps: Mix the dual-ligand Zn-MOF, epoxy cyclohexyl-cage polysilsesquioxane and dimethyl sulfoxide in a reaction kettle, stir magnetically at 75-85° C. for 6-8 hours under nitrogen protection, add sodium p-hydroxybenzenesulfonate to the reaction kettle, heat to 110-120° C. for reaction for 3-4 hours, then add acidified carbon nanotubes to the reaction kettle, react at constant temperature for 1-2 hours, add ethylenediamine after cooling to room temperature, stir and react for 18-24 hours, centrifuge and wash with deionized water and ethanol respectively, and vacuum dry at 70-80° C. to constant weight to obtain a modified composite filler; The dual-ligand Zn-MOF is prepared by the following steps: In a reaction kettle, 2-hydroxybenzimidazole and polyvinyl pyrrolidone were dissolved in methanol respectively and mixed, and then zinc nitrate hexahydrate was dissolved in methanol and dripped into the reaction kettle and stirred, and stirred at 65-75°C for 1-2h, and the solid was collected after centrifugation, washed with methanol, and vacuum dried to obtain a dual-ligand Zn-MOF; The acidified carbon nanotubes are prepared by the following steps: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 3:1 to prepare a mixed acid solution, and then multi-walled carbon nanotubes are mixed with the mixed acid solution in a dosage ratio of 1 g: 100 mL, and ultrasonic stirring is performed at a temperature of 50-60° C. for 2-3 hours, and a precipitate is obtained by centrifugation, and the acidified carbon nanotubes are obtained after washing and vacuum drying.
2. The acid- and alkali-resistant fluororubber according to claim 1, characterized in that: The dosage ratio of the dual ligand Zn-MOF, epoxy cyclohexyl-cage polysilsesquioxane, dimethyl sulfoxide, sodium p-hydroxybenzenesulfonate, acidified carbon nanotubes and ethylenediamine is 5-8g: 2-3g: 80-100mL: 0.5-1g: 5-8g: 150-200mL.
3. The acid- and alkali-resistant fluororubber according to claim 1, characterized in that: The usage ratio of the 2-hydroxybenzimidazole, polyvinyl pyrrolidone and zinc nitrate hexahydrate is 3-6g:8-10g:12-15g.
4. The method for preparing an acid- and alkali-resistant fluororubber according to claim 1, characterized in that: The following steps are involved: Step 1, mixing fluorinated rubber and tetrafluoroethylene rubber on an open mill at 60-65° C. for 4-6 minutes to obtain a mixed rubber, adding the modified composite filler to the mixed rubber at 80-95° C. for 6-8 minutes, and then adding benzoyl peroxide at 100-110° C. for 3-5 minutes to obtain a mixed rubber; Step 2: Roll the mixed rubber on an open rubber mixer with a thickness of 2-4 mm. Place the mixed rubber on a open mixer for 12-16 hours and then thin it in a triangle bag on the mixer for 10-15 times. Vulcanize the sample on a 45T flat vulcanizer, vulcanize at 173-177°C for 10 minutes and at 230°C for 24 hours to obtain acid and alkali resistant fluororubber.
5. Use of the acid- and alkali-resistant fluororubber according to claim 1 in electric vehicle battery sealing rubber.
Citation Information
Patent Citations
Chloroprene / tetrafluoroethylene-propylene rubber composite cable sheath material for ships and preparation method thereof
CN103509215A
Metal organic framework / multilayer carbon composite wave-absorbing material and preparation method thereof
CN113174143A
Macroporous Zn-MOF-PVP in-situ encapsulated beta-glucosidase compound as well as preparation method and application thereof
CN118028282A